Assessing the effectiveness of continuous glucose monitoring compared with conventional monitoring in enhancing surgical outcomes for patients with diabetes: protocol for a multicentre, parallel-arm, randomised, pragmatic trial in China - Han Cao; Yi Duan; Huan Zhang; Lin Ding; Lan Yao; Yutong Wang; Zhifeng Gao (BMJ Open)
Introduction The Comprehensive Complication Index (CCI) is an internationally recognised indicator of postoperative complications. During the perioperative period, patients with diabetes mellitus (DM) or impaired glucose tolerance (IGT) may experience a significant increase in the CCI associated with glucose-related complications and increased mortality. Continuous glucose monitoring (CGM) offers advantages such as portability, accuracy, real-time monitoring and rich information. However, few large-scale studies have investigated the effectiveness and safety of CGM in reducing CCI during major surgeries.Methods and analysis This study is a multicentre, parallel-arm, randomised pragmatic trial to investigate whether CGM improves clinical outcomes in patients with type 1 or type 2 DM or IGT undergoing major surgery relative to conventional monitoring. This study is planned to be conducted in 50 secondary or tertiary hospitals in China. Eligible patients aged 18 years or older with DM or IGT undergoing elective major surgery will be recruited during a baseline screening period of 3 days before surgery. Eligible patients will be randomly assigned to receive CGM or conventional monitoring in a 1:1 ratio. The primary endpoint measure is the CCI score within 30 postoperative days. The margin of superiority is −12.0. A total of 10 168 participants will achieve 90% power to detect a clinically important difference of −13.0 between the means in the primary outcome. This trial includes multiple statistical analysis steps. For the primary outcome, a covariance model will be used to compare the difference in CCI within 30 days postoperatively between the two groups after adjusting for baseline and centre effects.Ethics and dissemination This trial has been approved by the Ethics Committee of Beijing Tsinghua Changgung Hospital (No. 23684-0-02) and its corresponding branch centres. Informed consent will be obtained from all subjects involved in the study. The primary trial results will be submitted for publication to a peer-reviewed journal.Trial registration number NCT06331923.